The Use of Blockchain Technology for Smart Contracts in Future Business Agreements - Williams, Jacob; Anastasya, Luna; Juliastuti, Dyah; Ovaliani Putri, Claudia (Blockchain Frontier Technology, 2024)
The rapid advancement of technology in the digital era has prompted many companies to develop their businesses in line with current trends, one of which is by applying blockchain technology to smart contracts. This technology is a derivative of Cryptocurrency, which has become a trend in asset trading. The blockchain system in Cryptocurrency enables smart contracts to be designed to operate autonomously through blockchain technology using programming languages translated into legal language. This study aims to analyze the legality of using blockchain technology for smart contracts as legal products in the digital era and to assess the effectiveness of blockchain technology on smart contracts in business agreements between companies in Indonesia. This research employs a normative juridical method, focusing on the prevailing legal regulations related to the legality and effectiveness of using blockchain technology in smart contracts. The study concludes that the potential of blockchain for smart con- tracts is significant, given its efficiency and practicality, which can also reduce transaction costs. However, its implementation still needs to adapt to existing technologies, be easily accepted by society, and have stronger legal guarantees in its application.